Functional Microparticles – "LEGO" for Printable Bioelectronics Richard Newell. (2017) - Wannapob, Rodtichoti; Vagin, Mikhail; Liu, Yu; Turner, Anthony P.F.; Cheung, Mak Wing
Abstract: The current trend towards flexible and light-weight portable electronic devices has raised the profile of the emerging field of printed electronics. Printable organic electronic devices provide a high-throughput and cost-effective approach for the fabrication of distributed healthcare devices, which will meet new market needs. Here, we present an innovative modular approach for the design and fabrication of printable biosensors. A "LEGO" style approach comprising various colloidal building blocks, such as conducting polymer-based microparticles and biopolymer-based microparticles (e.g. enzymes and antibodies) with well-defined and tunable nano-scale morphology, electrochemical behaviours and catalytic functions, were fabricated for the development of printable biosensors. Assembly of the printable biosensors can be performed simply by mixing various microparticles delivering the desired conductivity, capacitance, catalytic and affinity functions, followed by solvent-free printing of the microparticle mixture onto a substrate. The conductivity, capacitance and signal response of the printable biosensors were characterised. This modular approach allows high flexibility for the design for biosensors, as well as better integration between conducting polymers and biomolecules for the development of biosensors. As a proof-of-concept, a mediated glucose biosensor based on printable microparticles was developed and showed a high sensitivity of 2 mA (M cm 2 ) -1 .